2010
DOI: 10.1080/00140139.2010.519125
|View full text |Cite
|
Sign up to set email alerts
|

Higher mental stimulation at work is associated with improved cognitive functioning in both young and older workers

Abstract: The study examined whether mental stimulation received in the workplace positively affects cognitive functioning and rate of cognitive change. Data taken from the VISAT (ageing, health and work) longitudinal study concerned 3237 workers who were seen three times (in 1996, 2001 and 2006) and who were aged between 32 and 62 years at baseline. Measures of cognitive stimulation both at work and outside work were available at baseline. Cognitive efficiency was assessed on the three occasions through episodic verbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 41 publications
4
62
1
8
Order By: Relevance
“…This suggests that cognitive experiences across the life span may influence cognitive reserve in old age. 11,23 We are aware of previous studies linking cognitive activity 24 and occupational complexity 25,26 during middle age to late-life cognitive change but not studies linking childhood cognitive activity to late-life cognitive change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that cognitive experiences across the life span may influence cognitive reserve in old age. 11,23 We are aware of previous studies linking cognitive activity 24 and occupational complexity 25,26 during middle age to late-life cognitive change but not studies linking childhood cognitive activity to late-life cognitive change.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that cognitive experiences across the life span may influence cognitive reserve in old age. 11,23 We are aware of previous studies linking cognitive activity 24 and occupational complexity 25,26 during middle age to late-life cognitive change but not studies linking childhood cognitive activity to late-life cognitive change.Neuroimaging research suggests that cognitive activity can lead to changes in brain structure and function that might enhance cognitive reserve. Thus, occupations (e.g., professional musician, 27 London taxi driver 28 ) and leisure activities (e.g., playing Baduk 29 ) that challenge particular cognitive functions are associated with differences in the gray and white matter of brain regions that support the cognitive functions.…”
mentioning
confidence: 99%
“…Furthermore, in a recent longitudinal study Marquié et al (2010) analyzed performance in cognitive tasks as a function of cognitive work demands in about 3000 workers. The authors could show that the more cognitively stimulating the work the higher the scores in tests of episodic memory, attention and speed of processing, and the more favorable the change of these functions over a 10-year followup.…”
Section: Cognitive Functions and The Type Of Workmentioning
confidence: 99%
“…Challenging work represents such an important cognitive stimulation (Alvarado et al 2002;Bosma et al 2002;Marquié et al 2010;Wild-Wall et al 2009) which considerably reduces the risk of dementia in older age (Andel et al 2005;Lee et al 2010;Stern et al 1994;Swaab and Bao 2011).…”
Section: Cognitive Functions and The Type Of Workmentioning
confidence: 99%
“…Three studies found a positive association, [170][171][172] and two studies found no association (60% consistency). 173,174 Different markers of inflammation, e.g. C-reactive protein [170][171][172][173][174] or interleukin-6 [170][171][172][173] ), make comparisons of individual studies difficult.…”
Section: Inflammationmentioning
confidence: 99%